Ice sheet loads on marina piles - Doud, Jerry O. (Canadian Geotechnical Journal, 1978)
Two marina piles were instrumented with steel sleeves. The steel sleeves were fixed rigidly to the top of the piles. The bottoms of the sleeves were free to freeze into the ice sheet. Two transducers were placed on each sleeve above the water level to measure the vertically acting tension and compression forces imposed on the pile by the ice sheet. The testing took place during two winters at Ontonagon, Michigan, U.S.A.It was found that the fluctuating water level in the lake can produce large cyclical loads and that the vertical loading rate that an ice sheet imposes on a marina pile can be significant.